Identification of growth stage specific watering thresholds for drought screening in Solanum aethiopicum Shum - Nakanwagi, Mildred Julian; Sseremba, Godfrey; Kabod, Nahamya Pamela; Masanza, Michael; Balyejusa Kizito, Elizabeth (Scientific Reports, 2020)
Effective phenotyping for drought resistance is a pre-requisite for identification of modest crop varieties for farmers. For neglected and underutilized crops such as Solanum aethiopicum Shum group, no drought screening protocol based on rigorous iterations has been documented. A split-plot nested treatment structure was arranged in an experiment to identify growth stage-specific watering thresholds for this crop. Three plant growth stages (main plot; seedling, vegetative and flowering), watering regime at plant growth stage (2 regimes; well-watered and drought stressed) and day since last watering at plant growth stage were evaluated for soil moisture content (SMC), leaf wilting score (LWS), number of green leaves per plant (LPP) and leaf blade width (LBW). Highly significant differences (p < 0.001) were found at the different plant growth stages, watering regime (WR) within plant growth stage, and day within WR and plant growth stage. Under drought stress treatment, SMC declined exponentially at each stage. The earliest leaf wilting, reduction in LPP and LBW were generally observed at flowering followed by vegetative and slowest at the seedling stage. For future effective drought phenotyping studies in S. aethiopicum Shum and related crops, we recommend setting minimum drought stress treatments below 18% SMC at which the LWS is ≥2 at the vegetative.
Keywords: Growth stage; Watering thresholds; Drought screening; Solanum aethiopicum Shum